2016
DOI: 10.1007/s00592-016-0940-3
|View full text |Cite
|
Sign up to set email alerts
|

Is all hypoglycaemia treated as equal? An observational study of how the type of diabetes and treatment prescribed prior to admission influences quality of treatment of inpatient hypoglycaemia

Abstract: AimsInpatient hypoglycaemia is common and associated with adverse outcomes. There is often increased vigilance of hypoglycaemia in inpatients with type 1 diabetes (T1DM) compared to type 2 diabetes (T2DM). We aimed to investigate this apparent discrepancy, utilising the time to repeat (TTR) capillary blood glucose (CBG) measurement as a surrogate for engagement with guidelines stating that CBG should be rechecked following intervention within 15 min of an initial CBG of <4 mmol/L.MethodsThis is an observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(24 reference statements)
0
3
1
1
Order By: Relevance
“…In this regard, our findings align with the previous studies showing very low rates of adherence to this component of the hypoglycemia treatment protocol for hospitalized patients. 13-18 A study from the United Kingdom conducted from 2008 to 2013 found 8.9% had a repeat POCG within 15 minutes and a median (IQR) TTR of 80 (36-249) minutes, 13 indicating even lower rates of adherence compared to our US based study. Another study found that only 9% of patients had a TTR within 10 to 20 minutes of a hypoglycemic episode.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…In this regard, our findings align with the previous studies showing very low rates of adherence to this component of the hypoglycemia treatment protocol for hospitalized patients. 13-18 A study from the United Kingdom conducted from 2008 to 2013 found 8.9% had a repeat POCG within 15 minutes and a median (IQR) TTR of 80 (36-249) minutes, 13 indicating even lower rates of adherence compared to our US based study. Another study found that only 9% of patients had a TTR within 10 to 20 minutes of a hypoglycemic episode.…”
Section: Discussioncontrasting
confidence: 76%
“…Previous studies have demonstrated a strong association between the severity of hypoglycemia and TTR. 13,17,20 We evaluated the index POCG as a continuous measure and as a categorical variable according to the International Hypoglycemia Study Group consensus statement as follows: 54 to 70 mg/dL (mild/moderate) and 40 to 53 mg/dL (clinically significant). 27 Consistent with other studies, we considered <40 mg/dL to be severe hypoglycemia.…”
Section: Exposure Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28][29] En la categoría atención brindada al paciente la evidencia muestra que las personas diabéticas requieren un equipo de salud capacitado, que los ayude a generar control general de la enfermedad para evitar complicaciones como la hipoglucemia, mediante una atención personalizada, se recomienda atención por la especialidad de endocrinología, que permita el análisis efectivo de la situación clínica actual para establecer las metas terapéuticas deseadas con un régimen de medicamento adecuado. [30][31][32][33][34] En la categoría disminución de la hipoglucemia se evidencia en los estudios la implementación de intervenciones y planes de acción encaminados a la atención y educación del paciente con el objetivo de reducir la hipoglucemia en el paciente adulto con DM. [35][36][37][38][39][40] La categoría impacto de la hipoglucemia muestra que gran proporción de los pacientes presentan hipoglucemias severas, requiriendo así la asistencia de una ambulancia médica; frente a la hipoglucemia nocturna se evidenció que afecta potencialmente la capacidad del paciente para despertarse y responder con una ingesta adecuada de carbohidratos, entre otros síntomas.…”
Section: -26unclassified